DNA-GEL, Novel Nanomaterial for Biomedical Applications and Delivery of Bioactive Molecules - Lattuada, Enrico; Leo, Manuela; Caprara, Debora; Salvatori, Luisa; Stoppacciaro, Antonella; Sciortino, Francesco; Filetici, Patrizia (Frontiers in Pharmacology, 2020)
Novel DNA materials promise unpredictable perspectives for applications in cell biology. The realization of DNA-hydrogels built by a controlled association of DNA nanostars, whose binding can be tuned with minor changes in the nucleotide sequences, has been recently described. Such novel nanomaterials with tailored and unusual gelation properties can be successfully employed for in situ delivery of drugs and bioactive molecules in tissues. We provide here a comprehensive description of different, recently realized DNA-gels with the perspective of stimulating their application to biological systems and cell lines. Finally, we discuss the possibility to design sophisticated 3D tissue-like DNA-gels incorporating cell spheroids or single cells for the assembly of a novel kind of cellular matrix and as a preclinical investigation for the implementation of tools for in vivo delivery of bioactive molecules.